Racial Microaggressions and Sense of Belonging at a Historically White University. (July 2021) - Lewis, Jioni A.; Mendenhall, Ruby; Ojiemwen, Ashley; Thomas, Merin; Riopelle, Cameron; Harwood, Stacy Anne; Browne Huntt, Margaret
This study applied critical race theory to explore the racial microaggression experiences of students of color (i.e., African American, Asian American, Latinx, and Multiracial students) at a historically White university. Using quantitative and qualitative data from an online survey ( N = 1, 710), we explored the relationship between the frequency of racial microaggressions and sense of belonging using multiple regression analysis. In addition, we analyzed qualitative open-ended responses to better understand students' perceptions about how the racial microaggressions they experienced affected their sense of belonging. The findings indicated that African American students reported experiencing a significantly greater frequency of racial microaggressions than Asian American, Latinx, and Multiracial students. In addition, students who reported a greater frequency of racial microaggressions also reported lower sense of belonging. We highlight implications for future research on students of color at historically White universities.